2023
DOI: 10.1021/acsami.3c02408
|View full text |Cite
|
Sign up to set email alerts
|

Tannic-Acid-Enriched Poly(vinyl alcohol) Nanofibrous Membrane as a UV-Shie lding and Antibacterial Face Mask Filter Material

Abstract: Face masks are increasingly important in the battle against infectious diseases and air pollution. Nanofibrous membranes (NFMs) are promising filter layers for removing particulate matter (PM) without restricting air permeability. In this study, tannic-acid-enriched poly(vinyl alcohol) (PVA−TA) NFMs were fabricated by electrospinning PVA solutions containing large amounts of tannic acid (TA), a multifunctional polyphenol compound. We were able to prepare uniform electrospinning solution without coacervate form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Moreover, the TA-PFRN@Ag nanocomposites also exhibit high ultraviolet (UV) shielding. As shown in Figure S12a, the introduction of TA 5 -PFRN@Ag endowed the materials with excellent UV-blocking performance, which was attributed to the large amounts of phenolic–OH groups in TA and PFRN molecules . In Figure S12b, through the TA 5 -PFRN@Ag-containing PVA films, gold-colored fluorescence is not transmitted in UV-sensitive areas (Figure S12c).…”
Section: Resultsmentioning
confidence: 95%
“…Moreover, the TA-PFRN@Ag nanocomposites also exhibit high ultraviolet (UV) shielding. As shown in Figure S12a, the introduction of TA 5 -PFRN@Ag endowed the materials with excellent UV-blocking performance, which was attributed to the large amounts of phenolic–OH groups in TA and PFRN molecules . In Figure S12b, through the TA 5 -PFRN@Ag-containing PVA films, gold-colored fluorescence is not transmitted in UV-sensitive areas (Figure S12c).…”
Section: Resultsmentioning
confidence: 95%
“…Electrospun nanofibers, particularly those incorporating PVA, have emerged as versatile materials for advanced PPE development. Numerous studies have investigated the use of electrospun nanofibrous membranes in PPE applications, showcasing their potential for providing UV-shielding, antibacterial and antiviral properties, and high filtration efficiency [171][172][173][174]. Abbas et al developed a novel multilayer mask with a degradable, multifunctional hybrid filter composite.…”
Section: Filtrationmentioning
confidence: 99%
“…23 What is more, because TA-based materials are extremely durable in physiological settings and harmless to in vitro grown cells, they hold great promise for use in a variety of biomedical and other sectors. 24–28 In some previous studies, 29,30 it was demonstrated that the mechanical performances of PVA were greatly improved by the incorporation of TA. In addition, due to the addition of TA, the antibacterial properties of PVA hydrogel coatings have also been improved to a certain extent.…”
Section: Introductionmentioning
confidence: 99%